Gendered voices for climate action - and Fisher, Susannah; Shakya, Clare (iied Working Paper, 2018)
Including local women and men who have experienced the impacts of climate change in decision-making forums is key to developing a just process hearing local voices and experiences. The Paris Agreement signs up the international community to delivering countrydriven, gender-responsive climate action. Including local women and men will be critical to this transition and to achieving the scale and pace of change needed through both procedural and distributional justice. However, there is scarce evidence on how these voices and experiences can impact on and strengthen climate responses, or how best to enable and facilitate this participation.